Maceration Before and During Fermentation: Effect on Pinotage Wine Phenolic Composition, Total Antioxidant Capacity and Objective Colour Parameters - de Beer, D.; Joubert, E.; Marais, J.; Manley, M. (South African Journal of Enology and Viticulture, 2017)
Low-temperature maceration treatments (1, 2 and 4 days at 10 and 15°C) before fermentation and juice/skin mixing treatments (punching-down, pumping-over and rotor action every hour and every 3 hours) during fermentation were investigated in terms of their effects on Pinotage wine phenolic composition, total antioxidant capacity (TAC) and colour over three vintages (2000 to 2002). Results for pre-fermentation maceration were not consistent between vintages. Very few significant differences in the phenolic content, TAC and objective colour parameters were observed between the control wines and wines subjected to different pre-fermentation maceration treatments. Pre-fermentation maceration, especially at 15°C, resulted in wines with increased vitisin A content. Improvement of wine quality when using pre-fermentation maceration treatments at 10°C was noted previously, while no detrimental effect on the wine TAC was observed. The pumping-over treatment yielded wines with lower TAC and phenol content, as well as less favourable objective colour values, indicating that the punching-down or rotor treatment would be preferred. Although mixing at hourly intervals yielded a higher content of some phenolic compounds compared to the 3-hour interval mixing, mixing frequency did not affect the TAC of the wine. The objective colour parameters, h* and b*, were slightly lower at the higher mixing frequency in 2002 indicating a shift in the direction of a magenta hue.